Afterword (Editorial) - Kazuhisa Iwabuchi; Alessandro Prinetti (Glycoconjugate Journal, 2023)

Massive Accumulation of Sphingomyelin Affects the Lysosomal and Mitochondria Compartments and Promotes Apoptosis in Niemann-Pick Disease Type A - Emma Veronica Carsana; Giulia Lunghi; Simona Prioni; Laura Mauri; Nicoletta Loberto; Alessandro Prinetti; Fabio Andrea Zucca; Rosaria Bassi; Sandro Sonnino; Elena Chiricozzi; Stefano Duga; Letizia Straniero; et al. (Journal of Molecular Neuroscience, 2022)
Niemann-Pick type A disease (NPA) is a rare lysosomal storage disorder caused by mutations in the gene coding for the lysosomal enzyme acid sphingomyelinase (ASM). ASM deficiency leads to the consequent accumulation of its uncatabolized substrate, the sphingolipid sphingomyelin (SM), causing severe progressive brain disease. To study the effect of the aberrant lysosomal accumulation of SM on cell homeostasis, we loaded skin fibroblasts derived from a NPA patient with exogenous SM to mimic the levels of accumulation characteristic of the pathological neurons. In SM-loaded NPA fibroblasts, we found the blockage of the autophagy flux and the impairment of the mitochondrial compartment paralleled by the altered transcription of several genes, mainly belonging to the electron transport chain machinery and to the cholesterol biosynthesis pathway. In addition, SM loading induces the nuclear translocation of the transcription factor EB that promotes the lysosomal biogenesis and exocytosis. Interestingly, we obtained similar biochemical findings in the brain of the NPA mouse model lacking ASM (ASMKO mouse) at the neurodegenerative stage. Our work provides a new in vitro model to study NPA etiopathology and suggests the existence of a pathogenic lysosome-plasma membrane axis that with an impairment in the mitochondrial activity is responsible for the cell death.

Introduction: the Glycobiology of nervous system - Sandro Sonnino; Alessandro Prinetti (Glycoconjugate Journal, 2018)

Neuronal membrane dynamics as fine regulator of sphingolipid composition - Massimo Aureli; Maura Samarani; Nicoletta Loberto; Elena Chiricozzi; Laura Mauri; Sara Grassi; Domitilla Schiumarini; Alessandro Prinetti; Sandro Sonnino (Glycoconjugate Journal, 2018)

On the use of cholera toxin - Elena Chiricozzi; Laura Mauri; Maria Grazia Ciampa; Alessandro Prinetti; Sandro Sonnino (Glycoconjugate Journal, 2018)

Serum Antibodies to Glycans in Peripheral Neuropathies - Sandro Sonnino; Elena Chiricozzi; Maria Grazia Ciampa; Laura Mauri; Alessandro Prinetti; Gino Toffano; Massimo Aureli (Molecular Neurobiology, 2017)

GM1 Ganglioside: Past Studies and Future Potential - Massimo Aureli; Laura Mauri; Maria Grazia Ciampa; Alessandro Prinetti; Gino Toffano; Cynthia Secchieri; Sandro Sonnino (Molecular Neurobiology, 2016)

Exploring the link between ceramide and ionizing radiation - Massimo Aureli; Valentina Murdica; Nicoletta Loberto; Maura Samarani; Alessandro Prinetti; Rosaria Bassi; Sandro Sonnino (Glycoconjugate Journal, 2014)

Lipid Rafts in Neurodegeneration and Neuroprotection - Sandro Sonnino; Massimo Aureli; Sara Grassi; Laura Mauri; Simona Prioni; Alessandro Prinetti (Molecular Neurobiology, 2014)

Chaperone Therapy for GM2 Gangliosidosis: Effects of Pyrimethamine on β-Hexosaminidase Activity in Sandhoff Fibroblasts - Elena Chiricozzi; Natalia Niemir; Massimo Aureli; Alessandro Magini; Nicoletta Loberto; Alessandro Prinetti; Rosaria Bassi; Alice Polchi; Carla Emiliani; Catherine Caillaud; Sandro Sonnino (Molecular Neurobiology, 2014)

The Glycosphingolipid Hydrolases in the Central Nervous System - Massimo Aureli; Maura Samarani; Nicoletta Loberto; Rosaria Bassi; Valentina Murdica; Simona Prioni; Alessandro Prinetti; Sandro Sonnino (Molecular Neurobiology, 2014)

Ionizing radiations increase the activity of the cell surface glycohydrolases and the plasma membrane ceramide content - Massimo Aureli; Rosaria Bassi; Alessandro Prinetti; Elena Chiricozzi; Brigida Pappalardi; Vanna Chigorno; Nadia Di Muzio; Nicoletta Loberto; Sandro Sonnino (Glycoconjugate Journal, 2012)

Deregulated Sphingolipid Metabolism and Membrane Organization in Neurodegenerative Disorders - Marco Piccinini; Federica Scandroglio; Simona Prioni; Barbara Buccinnà; Nicoletta Loberto; Massimo Aureli; Vanna Chigorno; Elisa Lupino; Giovanni DeMarco; Annarosa Lomartire; Maria Teresa Rinaudo; Sandro Sonnino; et al. (Molecular Neurobiology, 2010)

Thin layer chromatography of gangliosides - Federica Scandroglio; Nicoletta Loberto; Manuela Valsecchi; Vanna Chigorno; Alessandro Prinetti; Sandro Sonnino (Glycoconjugate Journal, 2009)

Role of very long fatty acid-containing glycosphingolipids in membrane organization and cell signaling: the model of lactosylceramide in neutrophils - Sandro Sonnino; Alessandro Prinetti; Hitoshi Nakayama; Mitsuaki Yangida; Hideoki Ogawa; Kazuhisa Iwabuchi (Glycoconjugate Journal, 2009)

Brain lipid composition in grey-lethal mutant mouse characterized by severe malignant osteopetrosis - Alessandro Prinetti; Federica Rocchetta; Elvira Costantino; Annalisa Frattini; Elena Caldana; Francesca Rucci; Arianna Bettiga; Pietro L. Poliani; Vanna Chigorno; Sandro Sonnino (Glycoconjugate Journal, 2009)

Involvement of very long fatty acid-containing lactosylceramide in lactosylceramide-mediated superoxide generation and migration in neutrophils - Kazuhisa Iwabuchi; Alessandro Prinetti; Sandro Sonnino; Laura Mauri; Toshihide Kobayashi; Kumiko Ishii; Naoko Kaga; Kimie Murayama; Hidetake Kurihara; Hitoshi Nakayama; Fumiko Yoshizaki; Kenji Takamori; et al. (Glycoconjugate Journal, 2008)

Involvement of very long fatty acid-containing lactosylceramide in lactosylceramide-mediated superoxide generation and migration in neutrophils - Kazuhisa Iwabuchi; Alessandro Prinetti; Sandro Sonnino; Laura Mauri; Toshihide Kobayashi; Kumiko Ishii; Naoko Kaga; Kimie Murayama; Hidetake Kurihara; Hitoshi Nakayama; Fumiko Yoshizaki; Kenji Takamori; et al. (Glycoconjugate Journal, 2008)

Efflux of sphingolipids metabolically labeled with [1-3H]sphingosine, L-[3-3H]serine and [9,10-3H]palmitic acid from normal cells in culture - Vanna Chigorno; Mariateresa Sciannamblo; Joanna Mikulak; Alessandro Prinetti; Sandro Sonnino (Glycoconjugate Journal, 2006)

Interactions between gangliosides and proteins in the exoplasmic leaflet of neuronal plasma membranes: A study performed with a tritium-labeled GM1 derivative containing a photoactivable group linked to the oligosaccharide chain - Simona Prioni; Laura Mauri; Nicoletta Loberto; Riccardo Casellato; Vanna Chigorno; Domna Karagogeos; Alessandro Prinetti; Sandro Sonnino (Glycoconjugate Journal, 2004)

Synthesis of radioactive and photoactivable ganglioside derivatives for the study of ganglioside-protein interactions - Laura Mauri; Simona Prioni; Nicoletta Loberto; Vanna Chigorno; Alessandro Prinetti; Sandro Sonnino (Glycoconjugate Journal, 2003)

Association of Src-family protein tyrosine kinases with sphingolipids in rat cerebellar granule cells differentiated in culture - Alessandro Prinetti; Nadia Marano; Simona Prioni; Vanna Chigorno; Laura Mauri; Riccardo Casellato; Guido Tettamanti; Sandro Sonnino (Glycoconjugate Journal, 2000)

New approaches to the study of sphingolipid enriched membrane domains: The use of microscopic autoradiography to reveal metabolically tritium labeled sphingolipids in cell cultures - Vincenza Dolo; Sandra D'Ascenzo; Maurizio Sorice; Antonio Pavan; Mariateresa Sciannamblo; Alessandro Prinetti; Vanna Chigorno; Guido Tettamanti; Sandro Sonnino (Glycoconjugate Journal, 2000)